The rehabilitation experiences, individual and combined effects of cognitive and physical rehabilitation on health and social outcomes in older athletes: A scoping review protocol - Alexander Wakim; Kelvin Somoto Utazi; Nelson E. Ekechukwu; Michael E. Kalu (PLoS ONE, 2026)
Background Evidence indicates that combined cognitive and physical rehabilitation can yield substantial improvements in health and social outcomes within the general aging population. However, the specific effects of such interventions on older athletes, who often exhibit enhanced resilience due to their competitive training backgrounds, remain inadequately explored. Objectives This study aims to describe the treatment regime (frequency, intensity, time/duration, and type of volume and progression of rehab) and components of cognitive and physical rehabilitation interventions, describe their combined effects on health and social outcomes and explore older athletes’ experiences with these interventions. Methods We will conduct a systematic scoping review following the five stages of the Arksey and O'Malley Framework. The search strategy will be developed in collaboration with a health and rehabilitation librarian, and searched in multiple data bases: MedLine, Web of Science, ProQuest, EBM Reviews, JBI EBP, Embase, APA PsychInfo, and Social Services Abstracts. Multiple reviewers will screen titles and abstracts, followed by full-text assessments in COVIDENCE, utilizing predefined inclusion and exclusion criteria. Articles will be included if participants were older athletes who actively engage in organized sports, characterized by regular competition and systematic training, and who have undergone cognitive and physical rehabilitation interventions. Data extraction will occur in pairs, focusing on relevant information to fulfill the study objectives. The pilot testing of all components—titles, abstracts, full texts, and data extraction protocols—will be conducted prior to the main review process. We will categories the physical and cognitive interventions using as frequency, intensity, time/duration, type of volume, progression of rehabilitation, and type of exercise. Additionally, data on intervention effects, including effect size and mean differences, will be summarized narratively. The experiences of the older athletes would be thematically analyzed. Discussion This scoping review will provide valuable information for clinicians, researchers, and policymakers to develop combined physical and cognitive rehabilitation programs tailored to the distinct physiological, cognitive and social needs of older athletes.